ANALISIS KOMBINASI PEMBELAJARAN MODUL, E-MODUL, DAN GAYA BELAJAR TERHADAP HASIL BELAJAR BIOLOGI - Larasati, Anggia Dwi; Sujarwanta, Agus (BIOLOVA, 2020)
Learning outcomes are the final acquisition of the learning process. Learning outcomes are the limits owned by students in understanding the material. Good learning outcomes can reflect a good learning style because knowing and understanding the best learning styles for him will help students learn so that the results will be maximal. The purpose of this study is to determine the effect of the combination of learning modules on learning outcomes, the influence of learning styles on learning outcomes, and the effect between the combination of learning modules and learning styles on learning outcomes. The technique used to collect data about student learning outcomes, the tests carried out are formative tests. Forms of the questions used are multiple choice questions compiled with a grid that refers to competency standards and basic competencies. Data analysis technique that will be used to test the hypothesis in this study is to use inferential parametric statistics by using the Anova two way classification analysis technique. Before testing the hypothesis, normality and homogeneity of the data are tested as a prerequisite for data analysis. Based on the research conducted, it can be concluded that the e-modules studied are feasible to be used as one of the reference teaching materials in learning biology in schools.